PENGARUH STRES KERJA TERHADAP KINERJA ORGANISASI PADA SEKTOR KESEHATAN - Dhiyaa Ulhaq; Aqeela Nandita Putri, Rafa Aurelia Maritza, Dinda Putri Ramadhani, Raina Rahmawati Ariana, Fara Asna (Jurnal Ekonomi dan Bisnis, 2025)
Performance refers to the results achieved by an organization, whether profit-oriented or non-profit-oriented, within a certain period of time. Performance also reflects work results that are closely related to the organization's strategic goals, customer satisfaction, and contribution to economic aspects. This study uses a literature review method with data sources from journals obtained through Google Scholar and OpenKnowledge. Factors that trigger stress include excessive workload, pressure and unfair treatment from leaders, limited time and work facilities, conflicts between individuals, leaders, and work groups. The results of a review of several journals show that the implementation of health workers' duties still faces obstacles, because they often have dual responsibilities that are not in accordance with standard procedures. This causes the monthly reports they make to be often incomplete, so that the reports sent to the health office are less accurate, and the results are often uniform every month. This study aims to analyze the impact of work stress on the performance of health workers. The population and sample of the study included all health workers in health centers and hospitals. To overcome the influence of work stress on performance, it is recommended that work programs be adjusted to the duties and professions of each health worker. This is expected to reduce work stress levels and improve the quality of their performance.